THE CONNECTIONS AND DIFFERENCES BETWEEN MYTHOLOGY AND FOLKLORE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article provides information about myths and their origin, what a myth is and in what sense it is used. In addition, the main purpose of the article is to determine the relationship between mythology and folklore, their similarities, and the difference between mythology and folklore. In addition, the article contains the opinions of mythologists and folklorists.